Implementasi Algoritma Dijkstra dan Greedy dalam Penyelesaian Masalah Rute Terpendek - Angul, Angelina; Fallo, Diana; Tanggo, Karolina Viviliana; Belo, Ivonia Nazario Alves; Hoar, Fenesia (Jurnal Kridatama Sains dan Teknologi, 2025)
The shortest route problem is a classic topic in graph theory that has many applications in everyday life, such as in navigation systems, logistics distribution, and network management. Two algorithms that are often used are the Algorithm and the Greedy Algorithm. The Algorithm can find the shortest path with maximum results, but it has a fairly high time complexity, making it less effective for situations that require speed. On the other hand, the Greedy Algorithm can provide solutions quickly, but does not always produce the ideal shortest path. This study uses a systematic literature review (SLR) approach to scientific publications in 2020-2025, which aims to analyze and compare the performance of the two algorithms in depth. The results of the analysis show that the Algorithm is more appropriate for situations that prioritize optimal solutions, while the Greedy Algorithm is better at decisions that require speed. This study not only provides theoretical analysis, but also discusses its practical applications in the transportation, logistics, and network sectors, and aims to provide insight into the development of more efficient and effective systems in the future